Effectiveness of nail bed repair in children with or without replacing the fingernail: NINJA multicentre randomized clinical trial. Issue 4 (22nd March 2023) - Jain, Abhilash; Greig, Aina V H; Jones, Amy; Cooper, Cushla; Davies, Loretta; Greshon, Akiko; Fletcher, Heidi; Sierakowski, Adam; Dritsaki, Melina; Nguyen, Thi Thu An; Png, May Ee; Stokes, Jamie R; et al.
Abstract: Background: Surgery for nail bed injuries in children is common. One of the key surgical decisions is whether to replace the nail plate following nail bed repair. The aim of this RCT was to assess the clinical effectiveness and cost-effectiveness of nail bed repair with fingernail replacement/substitution compared with repair without fingernail replacement. Methods: A two-arm 1 : 1 parallel-group open multicentre superiority RCT was performed across 20 secondary-care hospitals in the UK. The co-primary outcomes were surgical-site infection at around 7 days after surgery and cosmetic appearance summary score at a minimum of 4 months. Results: Some 451 children presenting with a suspected nail bed injury were recruited between July 2018 and July 2019; 224 were allocated to the nail-discarded arm, and 227 to the nail-replaced arm. There was no difference in the number of surgical-site infections at around 7 days between the two interventions or in cosmetic appearance. The mean total healthcare cost over the 4 months after surgery was €84 (95 per cent c.i. 34 to 140) lower for the nail-discarded arm than the nail-replaced arm ( P < 0.001). Conclusion: After nail bed repair, discarding the fingernail was associated with similar rates of infection and cosmesis ratings as replacement of the finger nail, but was cost saving. Registration number: ISRCTN44551796 (http://www.controlled-trials.com ). Abstract : Nail bed injuries in children are common. This study shows that, after performing a nail bed repair, it is more expensive to replace the nail plate and provides no benefit over discarding it.